Incontro con Ferruccio Malandrini - Bonetti, Maria Francesca (Rivista di studi di fotografia. Journal of Studies in Photography, 2015)
This interview with Ferruccio Malandrini, one of Italy’s major collectors of historical photographs, sheds new light on the making of his collection, presently owned by Raccolte Museali Fratelli Alinari and Fondazione Monte dei Paschi di Siena. Malandrini discusses the history and rationale of his acquisitions, as well as the important exhibitions, publications, and historical work based on his collection. The interview offers a collector’s view on the development of photographic culture and the preservation of photographic heritage in post-WWII Italy.